Bibliometric and visual analysis of blood-testis barrier research - Yifeng Shen; Yaodong You; Kun Zhu; Chunyan Fang; Xujun Yu; Xujun Yu; Degui Chang (Frontiers Media S.A., 2022)
Background: Extensive research on the blood-testis barrier has been undertaken in recent years. However, no systematic bibliometric study has been conducted on this subject. Our research aimed to identify the hotspots and frontiers of blood-testis barrier research and to serve as a guide for future scientific research and decision-making in the field.Methods: Studies on the blood-testis barrier were found in the Web of Science Core Collection. VOSviewer, CiteSpace, and Microsoft Excel were used to conduct the bibliometric and visual analyses.Results: We found 942 blood-testis barrier studies published in English between 1992 and 2022. The number of annual publications and citations increased significantly between 2011 and 2022, notably in the United States. China and the United States, the US Population Council, Endocrinology, and Cheng C. Yan were the most productive countries, institution, journal, and author, respectively. The study keywords indicated that blood-testis barrier research involves a variety of compositional features (tight junctions, cytoskeleton, adherens junctions), cell types (Sertoli cells, germ cells, Leydig cells, stem cells), reproductive toxicity (cadmium, nanoparticles, bisphenol-a), and relevant mechanisms (spermatogenesis, apoptosis, oxidative stress, dynamics, inflammation, immune privilege).Conclusion: The composition and molecular processes of the blood-testis barrier as well as the blood-testis barrier in male infertility patients are the primary research hotspots in this field. In addition, future research will likely focus on treatment and the development of novel medications that target signal pathways in oxidative stress and apoptosis to preserve the blood-testis barrier. Further studies must extend to clinical diagnosis and therapy.